1999
DOI: 10.1128/jcm.37.12.3844-3850.1999
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Molecular Analysis of Rifampin-Resistant Mycobacterium tuberculosis Strains Isolated in Australia

Abstract: To develop a better understanding of the epidemiology and molecular biology of rifampin-resistant Mycobacterium tuberculosisstrains in Australia, 50 clinical isolates (33 rifampin-resistant and 17 rifampin-sensitive strains) cultured between 1990 and 1997 were analyzed by a number of bacteriological and molecular techniques. Examination of the drug resistance profiles of the 33 rifampin-resistant isolates revealed that 91% were resistant to rifampin in combination with resistance to isoniazid, 88% were resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 33 publications
6
24
2
1
Order By: Relevance
“…The frequencies of mutations in rpoB codons 516 (5.4%), 526 (15%) and 531 (71%) of the Beijing family isolates are similar to those reported for isolates in the north-west region of Russia [13] and the Archangel region [17]. The mutation 531TTG in rpoB is the most commonly observed mutation in rifampicin-resistant isolates in many parts of the world, e.g., in Brazil (54%) [24], the USA (35%) [25], India (38.7%) [26], Germany (65%) [27] and Australia (52%) [28]. The predominance of mutations in rpoB codon 531 of the rifampicin-resistant isolates belonging to the Beijing family is in good agreement with frequencies of mutations in codons of the rpoB gene and rates of growth of spontaneous rifampicin-resistant mutants of M. tuberculosis strain H37Rv [29], and Mycobacterium leprae, Mycobacterium africanum and Mycobacterium avium strains [30].…”
Section: Discussionsupporting
confidence: 77%
“…The frequencies of mutations in rpoB codons 516 (5.4%), 526 (15%) and 531 (71%) of the Beijing family isolates are similar to those reported for isolates in the north-west region of Russia [13] and the Archangel region [17]. The mutation 531TTG in rpoB is the most commonly observed mutation in rifampicin-resistant isolates in many parts of the world, e.g., in Brazil (54%) [24], the USA (35%) [25], India (38.7%) [26], Germany (65%) [27] and Australia (52%) [28]. The predominance of mutations in rpoB codon 531 of the rifampicin-resistant isolates belonging to the Beijing family is in good agreement with frequencies of mutations in codons of the rpoB gene and rates of growth of spontaneous rifampicin-resistant mutants of M. tuberculosis strain H37Rv [29], and Mycobacterium leprae, Mycobacterium africanum and Mycobacterium avium strains [30].…”
Section: Discussionsupporting
confidence: 77%
“…Although different susceptibility testing methods have been used, and some discrepancies have been reported, such studies have generally revealed a strong correlation between certain rpoB mutations and the MICs of rifampicin and rifabutin. According to these previous studies, all rifampicin-resistant isolates with Asp516Val or Asp516Tyr substitutions were susceptible to rifabutin, with the exception of two isolates reported by Yuen et al [14] with MICs of > 1 mg ⁄ L. In the present study, three isolates with Asp516Val or Asp516Tyr substitutions were also found to be rifabutin-susceptible. Rifampicinresistant isolates with His526Tyr, His526Asp, His526Arg or His526Pro substitutions and mutations at codons 513 and 531 were almost always resistant to rifabutin.…”
supporting
confidence: 66%
“…Rifampicinresistant isolates with His526Tyr, His526Asp, His526Arg or His526Pro substitutions and mutations at codons 513 and 531 were almost always resistant to rifabutin. However, two isolates with a Ser531Leu mutation were reported as rifabutinsusceptible by Yang et al [13] and Yuen et al [14]. In the present study, all isolates with the mutations mentioned above were resistant to rifabutin.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…Nevertheless, DNA sequencing is the technique of choice according to several studies on the genotypic detection of resistant TB strains. It has been applied to isolates from a wide variety of geographic origins, in the search for mutations in multiple loci of: MDR strains [23], RIF-r in rpoB [8,9,[24][25][26], RIF-r outside the RRDR core [27], INH in ndh [28], and katG [29], and EMB-r [17,30,31].…”
Section: Pcr-dna Sequencingmentioning
confidence: 99%